ANALYSIS OF CRYPTOCURRENCY AS A NEW CURRENCY WITH THE MAQASHID SHARIA APPROACH - Setiawan, Hendra (Komitmen: Jurnal Ilmiah Manajemen, 2025)
Cryptocurrency is a technology and financial innovation that has brought about significant changes in the economic sector. Its existence and use in the perspective of Sharia are still debatable. This study aims to analyze cryptocurrency with the Maqashid Sharia approach. They are covering the protection of religion, soul, mind, descendants, and property. This analysis uses a qualitative research method with a descriptive-analytical approach. Data were collected from various recent journals and books by experts discussing Cryptocurrency and Maqashid Sharia and then sorted and analyzed for their relationship. The results of this research provide a more comprehensive understanding of the suitability of cryptocurrency as a new currency with the maqashid sharia approach.